Staying Healthy Abroad: Supporting Migrant Workers through Nutrition and Health Screening - Herlin Ajeng Nurrahma; Fitria Endah Janitra (Jurnal Pengabdian Masyarakat Kedokteran, 2026)
Indonesian migrant workers in Taiwan, particularly those employed in domestic caregiving roles, are at risk of developing undiagnosed metabolic conditions due to long working hours, limited access to nutritious food, and insufficient health information. This community service program aimed to promote nutritional awareness and conduct early screening for metabolic risks among Indonesian migrant workers in Taipei. Implemented in June 2025 in collaboration with the Indonesian Muslim community (PCINU Taiwan), the program engaged 38 participants aged 25–55 years. Activities included anthropometric assessments, blood pressure measurements, random blood glucose testing, and a brief nutrition education session in Bahasa Indonesia. The results showed that 42.1% of participants had elevated blood glucose levels (140–199 mg/dL), and 5.3% reached the diabetes threshold (≥200 mg/dL). Blood pressure screening revealed that 28.9% were in the pre-hypertensive range and 7.9% had hypertension. Body mass index data indicated that 44.8% of participants were either overweight or obese. The culturally tailored education session was well-received, improving participants’ understanding of nutrition and practical steps for disease prevention. This program demonstrated the feasibility and impact of combining basic health screening with targeted health education for underserved migrant populations. It underscores the importance of early detection and culturally sensitive health promotion in preventing chronic diseases among migrant workers. Future efforts should expand such initiatives and integrate mental health and follow-up components to ensure sustainable community health support.